Prediction of Fetal Biliary Atresia Based on Second and Third-Trimester Ultrasound Characteristics - Zeng, Kaihui; Yang, Zeyu; Chen, Lizhu; Sun, Wie; Wang, Yu; Chen, Changyu; Cai, Ailu (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Objective To explore the diagnostic performance of prenatal ultrasound in the prediction of biliary atresia (BA).Methods We prospectively collected cases of suspected biliary abnormalities in the 2nd trimester of pregnancy and performed a series (at least 3) of prenatal ultrasound examinations in the 2nd and 3rd trimester. The presence of the gallbladder was examined each time, and its size and shape were assessed if the gallbladder was visible. The existence of other abnormalities was carefully evaluated. Neonatal ultrasound examination was conducted within 1 month after birth, and clinical data were followed-up for 6 months after birth.Results Among the 41 895 patients, 298 were suspected to have biliary abnormalities, while 82 patients were excluded due to loss to follow-up or induced labor caused by other abnormalities. A total of 216 patients were included in this study, and 15 were diagnosed with BA. We summarized the ultrasound findings of the gallbladders and defined a high-risk gallbladder for the prenatal diagnosis of BA. This was demonstrated to have the best diagnostic performance as a single parameter, with an area under the curve of 0.914 (95 %CI: 0.869–0.948). In addition, higher incidences of biliary cysts, right hepatic artery dilation, echogenic bowel, and ascites were observed in BA fetuses. Logistic regression analysis showed that the combination of 5 parameters had better diagnostic performance, with an area under the curve of 0.995 (95 %CI: 0.973–0.999).Conclusion The fetal gallbladder was found to be a critical feature for the identification of BA. Concomitant abnormalities could be helpful to improve the accuracy of the diagnosis.
Keywords: biliary atresia; gallbladder; fetus; prenatal diagnosis; ultrasound